Doing a literature review releasing the research imagination - Hart, Chris (London SAGE Publications, 2018)
The ultimate guide to the "what," "how," and "why" of literature reviewing, the Second Edition of the classic text shows how the literature review will unlock the full potential of one2s research.
The research imagination -- The purpose of literature reviewing -- Classifying and reading research to review -- Different types of literature review -- Argumentation analysis -- Evidence, evaluation and critical realism -- Understanding and analysing ways ideas are organized -- Mapping and analysing ideas -- Writing the review.
Includes bibliographical references (pages [315]-326) and index.
Keywords: Social sciences -- Research; Humanities -- Research; Report writing; Dissertations, Academic; Social sciences -- Research -- Handbooks, manuals, etc; Literature -- History and criticism